Тамада. Корпоративные праздники - Панкова Любовь Александровна (Серия "Экспресс - курс", 2006)
Экземпляры: аб. ЦБ (20181017) / Инвентарный номер: 5228 / Цена: / Сис.шифр: 85.34 / Авт.знак: П16 / ББК: 85.34